Topical and Intradermal Efficacy of Photodynamic Therapy with Methylene Blue and Light-Emitting Diode in the Treatment of Cutaneous Leishmaniasis Caused by Leishmania braziliensis - Sbeghen, Mônica Raquel; Voltarelli, Evandra Maria; Campois, Tácito Graminha; Kimura, Elza; Arisitides, Sandra Mara Alessi; Hernandes, Luzmarina; Caetano, Wilker; Hioka, Noboru; Lonardoni, Maria Valdrinez Campana; Silveira, ThaÃs Gomes Verzignassi (Journal of Lasers in Medical Sciences, 2015)
Introduction: The topical and intradermal photodynamic therapy (PDT) effect of methylene blue (MB) using light-emitting diode (LED) as light source (MB/LED-PDT) in the treatment of lesions of American cutaneous leishmaniasis (ACL) caused by Leishmania braziliensis in hamsters were investigated. Methods: Hamsters were infected in the footpad with 4×107 promastigotes of L. braziliensis and divided in 4 groups: Control group was not treated, AmB group was treated with amphotericin B, MB-Id group received intradermal MB at the edge of the lesion and MB-Tp group received MB topic. After treatment with MB, the animals were illuminated using red LEDs at the 655 nm wavelength for 1 hour. The MB/LED-PDT was carried out three times a week for 12 weeks. Results: Animals of MB-Tp group presented lesion healing with significant diminution in extent of the lesion, and reduced parasite burden compared to control group; however, no significant difference was seen compared to the AmB group. MB-Tp group also showed reconstitution of the epithelium, the formation of collagen fibers, organization in the epidermis, a little disorganization and inflammation in the dermis. MB-Id was ineffective in all parameters evaluated, and it was comparable to the control group results. Conclusion: These data show that PDT with the use of MB-Tp and LED may be an alternative for the treatment of ACL. However, additional studies are being conducted to assess the potential of MB/LED-PDT, alone or in combination with conventional therapy, for the treatment of ACL.